2000
DOI: 10.1099/00221287-146-6-1259
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide inhibits respiration yet stimulates aerobic growth of Zymomonas mobilis

Abstract: Potassium cyanide at submillimolar concentrations (20-500 µM) inhibited the high respiration rates of aerobic cultures of Zymomonas mobilis but, remarkably, stimulated culture growth. In batch culture, after an extended lag phase, exponential growth persisted longer, resulting in higher biomass densities. In aerobic chemostat cultures, elevated biomass concentration was observed in the presence of cyanide. This growth stimulation effect is attributed to decreased production of the inhibitory metabolite acetald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 31 publications
7
38
1
Order By: Relevance
“…It is well established that the maximum value of Y ETOH in Z. mobilis catabolism under anaerobic conditions is close to 0.51 g of ethanol per gram of consumed glucose [18,21], and that under aerobic growth conditions Y ETOH is lower due to competition for NADH between the respiratory chain and ethanol synthesis [15]. In the aerobic chemostat culture of the mutant strain, we found Y ETOH to be 0.22 g g À1 , which constitutes 43% of the maximum value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the maximum value of Y ETOH in Z. mobilis catabolism under anaerobic conditions is close to 0.51 g of ethanol per gram of consumed glucose [18,21], and that under aerobic growth conditions Y ETOH is lower due to competition for NADH between the respiratory chain and ethanol synthesis [15]. In the aerobic chemostat culture of the mutant strain, we found Y ETOH to be 0.22 g g À1 , which constitutes 43% of the maximum value.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol concentration was determined by gas chromatography (Varian). Acetaldehyde was assayed using the alcohol dehydrogenase reaction, and glucose was assayed with the glucose oxidase method, as described previously [15]. Cell concentration was determined as optical density at 550 nm, and dry cell mass of the suspensions was calculated by reference to a calibration curve.…”
Section: Methodsmentioning
confidence: 99%
“…Cyanide (1 mM) and azide (2 mM) inhibited both endogenous and substrate-dependent O 2 uptake up to 70% in whole-cell suspensions, indicating that most of the endogenous and exogenous substrate-dependent consumption of dioxygen follows an azide-and cyanide-sensitive pathway. Cyanide inhibition of O 2 consumption by whole cells has been reported in other bacteria, including acetogens (7,37,61).…”
Section: Dioxygen Uptake By Whole Cells and Membranesmentioning
confidence: 99%
“…Tano and Buzzato (2003) noted a low ethanol production (29 gL -1 ) by Z. mobilis in sugar cane juice during 24 hrs of fermentation in stirring condition. Anaerobic cultures of Z. mobilis have showed the highest ethanol yields (0.51 g glucose -1 ) in different substrates, while small yields (0.13 g glucose -1 ) have been noted in aerobic cultures (Kalnenieks et al 2000;Prasad et al 2007). Previous studies suggested a possible average yield of ethanol from mesquite pods of up to 260 L per ton, while for sugar cane it is purposed an average yield of up to 80 L per ton (Silva et al 2003, Silva et al 2007).…”
Section: Factorial Designmentioning
confidence: 99%